PEMANFAATAN TEPUNG BIJI DURIAN DAN TEPUNG KACANG HIJAU DALAM PEMBUATAN FLAKES - Luky Prasetyo; Akhyar Ali; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aimed to get the best ratio of durian seed flour and mung bean flour judging from the content of nutrients and organoleptic tests in making of flakes. The research was conducted with an experimental method using a Completely Randomized Design with five treatments and three replications. The treatments in this study were ratio of durian seed flour and mung bean flour 100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%. Data were statistically analyzed by using Analysis of Variance and followed by Duncan's New Multiple Range Test at level 5%. Results of the analysis showed that ratio of durian seed flour and mung bean flour significantly affected on moisture, ash, fat, protein, carbohydrate, and crude fiber content as well as descriptive and hedonic sensory test of the flakes. Based on this research, the best treatment was ratio of durian seed flour and mung bean flour 60%:40% which had moisture 4.28%, ash 3.51%, fat 1.29%, protein 10.45%, carbohydrate 80.46% and crude fiber 2.96%. Characteristics flakes of best treatment based on descriptive test was  golden yellow color, mung bean flavor, mung beantaste, andhard texture. Keywords:Flakes, durian seed flour, mung beanflour.